Importancia de la bacteria Lactobacillus Bulgaricus (Lactobacillus Delbrueckii Bulgaricus) sobre las características organolépticas nutricionales en el de queso y yogurt. - Hurtado Valero, Britany Keyla (2024)
Lactobacillus bulgaricus bacteria (Lactobacillus delbrueckii bulgaricus) are important microorganisms used in the production of fermented dairy products, such as yogurt, cheese, and others. These bacteria contribute to lactic fermentation that transform milk into dairy products with different organoleptic and nutritional characteristics. These bacteria are known for their ability to metabolize lactose and produce lactic acid, which acidifies the medium and provides an adverse environment for the growth of unwanted bacteria. In addition to their fermentative function, these bacteria also provide different sensory characteristics to the final product, including flavor and texture. It has multiple health benefits, when consumed one of them is the improvement of gastrointestinal health and strengthens the immune system. When consumed it provides us with benefits such as stimulating the immune system and helps stop the growth of pathogenic microorganisms, that is, helicobacter. These bacteria are classified by different types, normally found in the gastrointestinal tract, such as the mouth, vagina and skin, these lactobacillus bulgaricus bacteria are considered important bacteria since they help keep the body balanced and thus give many health benefits, of the consumer. In addition, this bacterium is used in the production of dairy products due to its fermentation capabilities in the product since they are used in the agroindustrial sector to produce products such as yogurt, cheese, butter, and others. Currently, different recognized companies in Ecuador already export these products to provide a quality product to the consumer.